An Analysis of Understanding Reading Argumentative Text For Students In Grade 7 SMP Gajah Mada - Afni Maylani; Yessy Octaviana; Febrika Dwi Lestari (Innovative: Journal Of Social Science Research, 2023)
The objective of this research was to find a solution to a phenomenon that is often found in junior high school students, that is reading argumentative texts. In this problem area, there are still many students who have difficulty understanding argumentative texts. This research was conducted in grade 7 off SMP Gajah Mada The participants in this study were students grade 7 from SMP Gajah Mada class A. the technique of selecting the sample is overall, where all members of the population have an equal and independent opportunity to be included in the research. Data collecting technique in this study will be carried out by testing. The test is conduct to find out how far students' understanding of argumentative text, The test is the first instrument, and it consist of 10 multiple choice questions. The result of this research indicate that the total score obtained by students from the test given is 1.170 with the mean score of 46,8 dan from the questionnaire the total students’ test score is 22 with the mean score of 4,4. The total students test score is 1.170 an the total of students observation score is 22, so the mean was 53,1. the ability of students in grade 7 of SMP Gajah Mada in reading argumentative text is considered still in developing stage.